Peripheral blood circular RNA hsa_circ_0124644 can be used as a diagnostic biomarker of coronary artery disease - Zhao, Zhenzhou; Li, Xuejie; Gao, Chuanyu; Jian, Dongdong; Hao, Peiyuan; Rao, Lixin; Li, Muwei (Scientific reports, 2017)
The aim of the present study was to investigate the expression of circular RNAs (circRNAs) in the peripheral blood of coronary artery disease (CAD) patients and the potential use of circRNAs as diagnostic biomarkers of CAD. We first analysed peripheral blood circRNAs of 12 CAD patients and 12 control individuals by RNA microarray and found that 22 circRNAs were differentially expressed between these two groups: 12 were upregulated, and 10 were downregulated. Then, we selected 5 circRNAs as candidate biomarkers under stricter screening criteria and verified them in another group of subjects consisting of 30 control individuals and 30 CAD patients with different SYNTAX scores. These 5 circRNAs were all remarkably increased in the CAD group. Hsa_circ_0124644 had the largest area under the curve (AUC). We tested hsa_circ_0124644 in an independent cohort consisting of 115 control individuals and 137 CAD patients. After we included the risk factors for CAD, the AUC slightly increased from 0.769 (95% confidence interval = [0.710–0.827], P < 0.001) to 0.804 ([0.751–0.857], P < 0.001), and when combined with hsa_circ_0098964, the diagnostic value slightly increased. Taken together, our results suggest that hsa_circ_0124644 can be used as a diagnostic biomarker of CAD.